Analisis Yuridis Cabang Pemerintahan Keempat “The Fourth Branch Of Government” dalam Struktur Ketatanegaraan di Indonesia - Tri Suhendra Arbani (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The development of the modern state system is also followed by the establishmentof new institutions as a support of the institutions that have been there before. The mostsignificant event in the development and establishment of institutions is the new powerbranch, which is called by the experts in constitutional as an independent statecommission. Independent state commission institution which, if seen from the characterand the authority, the agency in some literature in American constitutional law isreferred to as the fourth branch of power (The Fourth Branch of Government). Somethings that make this institution called the fourth branch of government (The FourthBranch of Government) is the fact that the agency, or commission or the state body runmore than one function of government as well. The existence of a fourth branch ofgovernment (The Fourth Branch of Government) with the characteristics of stateinstitutions whose authorities are quasi, combinations, as well as the accumulation ofthree existing government functions and make this institution to be difficult to identifyin thought Trias Politica. The phenomenon of the rise of an institution with a newconcept that has influenced the constitutional system in many countries.